Enhancing Value: The Impact of Environmental, Social, and Governance Disclosure on Indonesian Basic Materials Sector Companies - Difa, Amelia Putri Salma; Larasati, Anissa Yuniar (Jurnal Akuntansi, 2024)
Abstract Purpose - This study aims to determine the effect of the implementation of environmental, social and governance disclosure on firm value in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. Design/methodology/approach - This research uses quantitative methods using secondary data that has been published on the company’s official website and the official IDX website. The population in this study are basic materials sector companies listed on the IDX in 2018-2022. The samples in this study were 11 companies for five years of observation so that 55 data samples were obtained. The sampling technique used purposive sampling technique. The data analysis techniques used in the study are classical assumption test analysis, multiple linear regression test, correlation test, determination test, t test and f test using IBM SPSS 26 software. Findings - The results showed that environmental disclosure has a positive influence on firm value, but social disclosure and governance disclosure do not show the same positive influence on firm value.Research limitations/implications - The limited data set may not fully encapsulate the diverse impacts of ESG disclosures on firm value, thus impacting the robustness and generalizability of the study’s conclusions. Keywords: Environmental Disclosure, Social Disclosure, Governance Disclosure, and Firm Value